2020
DOI: 10.1177/0272989x20904725
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Health Risk Comprehension: The Role of Math Anxiety, Subjective Numeracy, and Objective Numeracy

Abstract: Background. Numeracy skills are important for medical decision making as lower numeracy is associated with misinterpreting statistical health risks. Math anxiety, characterized by negative emotions about numerical tasks, and lower subjective numeracy (i.e., self-assessments of numerical competence) are also associated with poor risk comprehension. Objective. To explore independent and mediated associations of math anxiety, numerical ability, and subjective numeracy with risk comprehension and to ascertain whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 56 publications
3
38
0
1
Order By: Relevance
“…Males had higher objective numeracy scores than females [t(905) = 7.20, p < 0.001, Cohen's d = 0.48], which is supported by prior work (Peters and Bjälkebring, 2015). More highly educated people also had greater objective numeracy (r = 0.177, p < 0.001), which is supported by prior work (Rolison et al, 2020).…”
Section: Exploratory Measuressupporting
confidence: 52%
“…Males had higher objective numeracy scores than females [t(905) = 7.20, p < 0.001, Cohen's d = 0.48], which is supported by prior work (Peters and Bjälkebring, 2015). More highly educated people also had greater objective numeracy (r = 0.177, p < 0.001), which is supported by prior work (Rolison et al, 2020).…”
Section: Exploratory Measuressupporting
confidence: 52%
“…Indeed, similar to other performance-based anxieties, MA involves psychological arousal, negative cognitions, escape and/or avoidance behaviors and, when the individual cannot avoid the situation, performance deficits. MA is also related to reduced cognitive reflection (Morsanyi et al, 2014;Primi et al, 2018), and poorer decision making performance (e.g., Rolison et al, 2016;Rolison et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the cognitive processes involved in the attitude toward mathematics have been scarcely studied. The research found relates the attitude toward mathematics to reasoning skills (Lipnevich et al, 2016), decisionmaking (Rolison et al, 2020), cognitive reflection (Morsanyi et al, 2014), and creativity (Sharma, 2014). Specifically, in the mathematical context, researchers pay more attention to creativity, which is considered as an action in the Creative Mathematics Action Framework (Riling, 2020) and as a thought process or product manifested in fluidity, cognitive flexibility, and originality (Fetterly, 2020).…”
Section: Cognitive Processes In the Attitude Toward Mathematicsmentioning
confidence: 99%